A Mountain of Content. An Early Look at Paramount+ and Its Strategies - Villani, Nicolò (The Matter of Intellectual Property: Studying the Economic, Political and Cultural Nodes of the Contemporary Media Industries. 15th Media Mutations International Conference, 2025)
Launched in the first territories in September 2021 and turned into a global portal in the following year, Paramount+ is the evolution of CBS All Access into a modern streaming portal. Paramount+ model results in a vertical integration by an IP-holding corporation in the direction of on-demand distribution, through a proprietary channel that allows it to have full control over products. Carrying a disparate constellation of brands, Paramount+ showcases an array of intellectual properties that digs into a vast legacy ground. In this, Paramount+ has so far operated, for its original contents and placement strategies that are still far from solid, reflecting the still quite acerbic functional nature of the portal itself. This paper examines Paramount+ early attempts at original content branding and its experimental transmedia expansion of IP; therefore, it aims to return a discursive picture of the direction the portal is taking via its content portfolios, assessing the effects of successes and failures. Due to territorialization reasons, the analysis of positioning is here carried out in the Italian context: this limitation becomes an opportunity for an initial assessment of the glocal dimension of the portal and to discuss the relationship between Paramount+ and Sky in the Italian context.